La Pedagogia di Aldo Braibanti nei prolegomeni acratici - Ilaria Barbieri Wurtz (Studi sulla Formazione)
The article aims to analyse the pedagogical contribution of Impresa dei prolegomeni acratici written by Aldo Braibanti. Against the power’ policies of his time, Braibanti emphasise the necessity of a “decentralisation” by forms of social and cultural influence. In this regard, the braibantian instance moves towards a “pedagogical revolution”, substantiated by an education to acracy and supported by an authentic ideal of freedom.